Plasma and erythrocyte fatty acids reflect intakes of saturated and n-6 PUFA within a similar time frame. - Hodson, L; Eyles, H; McLachlan, K; Bell, M; Green, T; Skeaff, C (2014)
Erythrocytes, compared with plasma, are considered more robust markers of n-3 (ω-3) polyunsaturated fatty acid (PUFA) intake, because dietary-induced change in fatty acid (FA) composition takes longer to complete. The extent to which this applies to intakes of saturated fatty acid (SFA) or n-6 PUFA is unclear. We compared the pattern of change over time in the fatty acid composition of plasma, erythrocyte, buccal cell, and adipose tissue lipids when changing between diets high in SFA or n-6 PUFA. Twenty-four (n = 7 male) healthy participants were instructed to consume either an SFA-rich (18% energy) or n-6 PUFA-rich (10% energy) diet for 8 wk before crossing over, without washout, to the alternate diet. The FA composition of plasma triacylglycerol (TG), nonesterified FAs, cholesterol ester, total phospholipids, erythrocyte total phospholipids, erythrocyte phosphatidylcholine, and buccal cell total phospholipids was measured every 2 wk and adipose tissue TG every 4 wk during the 16-wk intervention. Linoleic acid composition of plasma, erythrocyte, and buccal cell lipids increased (P < 0.01) during the first 2 wk of the n-6 PUFA diet and remained unchanged during the remaining 6 wk. During the 8-wk SFA diet, the same pattern of change over time occurred for the pentadecanoic acid composition of plasma and erythrocyte lipids; however, the pentadecanoic acid composition of buccal cell lipids did not differ between the diet periods. There were no differences in linoleic or pentadecanoic acid composition of adipose tissue TG. These results suggest plasma and erythrocyte FAs reflect intakes of SFA and n-6 PUFA over a similar period of time.